Experimental evidence on the effects of home computers on academic achievement among schoolchildren - Robert W. Fairlie; Jonathan Robinson (Institute for the Study of Labor (IZA), 2013)
Computers are an important part of modern education, yet large segments of the population - especially low-income and minority children - lack access to a computer at home. Does this impede educational achievement? We test this hypothesis by conducting the largest-ever field experiment involving the random provision of free computers for home use to students. 1,123 schoolchildren grades 6-10 in 15 California schools participated in the experiment. Although the program significantly increased computer ownership and use, we find no effects on any educational outcomes, including grades, standardized test scores, credits earned, attendance and disciplinary actions. Our estimates are precise enough to rule out even modestly-sized positive or negative impacts. The estimated null effect is consistent with survey evidence showing no change in homework time or other intermediate inputs in education for treatment students.
Keywords: I24; 330; computers; education; experiment